PENGARUH KUALITAS KOMUNIKASI KELUARGA TERHADAP STABILITAS EMOSI REMAJA - Siti Hoeriyah; Abdurohim (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Adolescence is a dynamic phase of development, both physically, cognitively, and emotionally. During this period, individuals are highly vulnerable to emotional instability due to social pressures and internal changes. One important factor influencing adolescents' emotional well-being is the quality of communication within the family. This study aims to explore the influence of family communication quality on adolescents' emotional stability using a qualitative approach through a literature review. The results indicate that families with open, warm, and supportive communication tend to produce more emotionally stable adolescents. Conversely, authoritarian, closed, or conflict-ridden communication patterns increase the risk of emotional disorders. This study recommends improving family communication literacy as a preventative measure to support adolescent mental health.